Revision of the diagnostic characters of two morphologically similar snook species, Centropomus viridis and C. nigrescens (Carangiformes: Centropomidae) - Martínez-Brown, Juan Manuel; Navarro-Flores, Jaime; García-Rodríguez, Francisco Javier; Ibarra-Castro, Leonardo; Vargas-Peralta, Carmen Elvira; Río-Portilla, Miguel Ángel Del; Martínez-Moreno, Rodrigo (Zootaxa, 2021)
Historically, the taxonomic identification of the two snook species, Centropomus viridis and C. nigrescens, has been challenging due to their morphological similarity and the inconsistency of the characters used for diagnosis. Therefore, this study aimed to evaluate the usefulness of the morphologic, meristic, and morphometric characters currently being used to identify C. viridis and C. nigrescens, based on molecular data. The results showed that the gas-bladder shape (i.e., C. viridis with diverticula and C. nigrescens without diverticula) was the only morphological character univocally related to genetic identification. Likewise, geometric morphometrics separated two groups; each corresponds to only one of two genetically (and gas bladder shape) identified species. Of all the meristic characters examined, only the second dorsal fin ray count (nine for C. viridis and ten for C. nigrescens) was related to the gas bladder shape and genetic identity; therefore, it is the only external character with a diagnostic utility to separate each species.